Gender Identity - Ribeiro, Maria Patrícia; Moreira, Diana; Coelho, Rui; Pereira, Altamiro; Almeida, Fernando (Advances in Social Sciences Research Journal, 2018)
The aim was to contribute to future research on Gender Identity associated with other domains of human reality, while looking to not forget that, over time, it was an essential topic in Arts and Sciences, reflecting a curiosity to define, interpret, and research “representations” of masculine and feminine roles regarding the “actors” (men or women) of the “acts”, as well as their “spectators” (the other men and women, who are all of us). Currently, there seems to be an intensifying of undifferentiation of the roles assigned to Gender, a kind of androgyny, though without this meaning the existence of internal resonance of this undifferentiation, as if one walked towards a narcissistic society, as if it were mental hermaphroditism.